A large direct simple shear device for the testing of peat at low stresses. Issue 4 (29th September 2014) - Den Haan, E. J.; Grognet, M.
Abstract : A large direct simple shear device has been developed for the testing of peat at low normal stress. The large size allows adequate representation of the often coarse structure of peat, increases the accuracy with which small loads can be applied and diminishes device resistances to acceptably small proportions. A plane strain configuration between glass plates is used, allowing observation of the deformation field as it develops. The sample is gripped by pins along all four in-plane boundaries to reduce slippage during shear. Interesting results have been obtained in an initial series of tests. Strengths appear to be some 10% higher than those in standard simple shear tests on small-diameter samples, while the post-peak softening often measured in the latter appears to be lacking.